Gainsbourg [videorecording (DVD)] : vie héroïque - Mouglalis, Anna; Elmosnino, Eric, 1964-; Casta, Laetitia, 1978-; Gordon, Lucy, 1980-2009; Amalric, Mathieu, 1965-; Sfar, Joann; Sfar, Joann (Music Box Films, 2012)
Best selling comic book artist Joann Sfar delivers an inventive biography of famed French singer Serge Gainsbourg. Born Lucien Ginsburg to Russian-Jewish parents, Sfar follows him from his childhood in Nazi-occupied Paris, his transition from painter to jazz musician to pop superstar and his many relationships including Juliette Greco, Brigitte Bardot, and Jane Birkin while employing a witty surrealistic style and a soundtrack that acts like a time capsule to '60s Paris.